Subclinical Hypothyroidism in Children: When a Replacement Hormonal Treatment Might Be Advisable - Crisafulli, Giuseppe; Aversa, Tommaso; Zirilli, Giuseppina; Pajno, Giovanni Battista; Corica, Domenico; De Luca, Filippo; Wasniewska, Malgorzata (Frontiers in Endocrinology, 2019)
Aim of this mini review was to analyze the main variables which should be taken into account when the decision regarding a possible treatment with L-T4 has to be considered for a child with subclinical hypothyroidism (SH). The indications of periodical monitoring and vigilance have been also discussed. It was inferred that therapy should be recommended for children with underlying Hashimoto’s thyroiditis and progressive deterioration of thyroid status over time, particularly in the cases with goiter and hypothyroid symptoms and in those with associated Turner syndrome or Down’s syndrome and/or other autoimmune diseases. Treatment might also be recommended for children with proatherogenic metabolic abnormalities. Treatment is not advisable in children with idiopathic and mild SH, no goiter, no hypothyroid symptoms and negative anti-thyroid autoantibodies. In the absence of any therapeutic intervention, clinical status and thyroid function tests should be periodically monitored, in order to individuate the children who might benefit from treatment. It has been suggested that children with a persistent mild elevation of TSH, who are not treated with L-T4, should undergo biochemical monitoring of thyroid function and re-assessment of clinical status every 6 months. After 2 years with stable thyroid function tests, the interval between monitoring can be extended.